2021
DOI: 10.1007/s00262-021-03080-6
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal flora of patients with GHPA affects the growth and the expression of PD-L1 of tumor

Abstract: Context Pituitary adenoma (PA) is a common intracranial tumor. The evidence indicates that the tumor immune microenvironment (TIME) is associated with PA and that the intestinal flora influences other tumors' growth through interacting with the TIME. However, how the intestinal microbial flora contributes to the development of PA through the immune response is unknown. Objective and methods Here we used high-throughput Illumina MiSeq sequencing targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…The authors postulated that the imbalanced Firmicutes/Bacteroidetes ratio may induce inflammation and deficiency of beneficial metabolites, such as butyrate. However, later research conducted in a different ethnicity found different species that were increased ( Enterococcus , Prevotella , and Bifidobacterium ) and decreased ( Faecalibacterium and Megamonas ) 100 . Due to the limitations of 16 S rRNA amplicon sequencing, our group further utilized the metagenomic sequencing in GHPA patients and observed increased abundance of Oscillibacter and Enterobacter , along with decreased abundance of Blautia and Romboutsia 101 .…”
Section: Aberrant Microbial Landscapes and Dysregulated Microbiota–gu...mentioning
confidence: 90%
See 2 more Smart Citations
“…The authors postulated that the imbalanced Firmicutes/Bacteroidetes ratio may induce inflammation and deficiency of beneficial metabolites, such as butyrate. However, later research conducted in a different ethnicity found different species that were increased ( Enterococcus , Prevotella , and Bifidobacterium ) and decreased ( Faecalibacterium and Megamonas ) 100 . Due to the limitations of 16 S rRNA amplicon sequencing, our group further utilized the metagenomic sequencing in GHPA patients and observed increased abundance of Oscillibacter and Enterobacter , along with decreased abundance of Blautia and Romboutsia 101 .…”
Section: Aberrant Microbial Landscapes and Dysregulated Microbiota–gu...mentioning
confidence: 90%
“…They found that fecal microbiota transplantation (FMT) from GHPA donors in tumor‐bearing nude mice increased tumor weight and volume, expanded PD‐L1 positive cell populations and CD8+ cell infiltration in tumor tissues, and increased levels of CD3 + CD8+ cell and sPD‐L1 in the peripheral circulation. This indicates that GHPA‐specific flora influences the status of the immune system, which may facilitate the escape of tumor cells from immune surveillance 100 …”
Section: Aberrant Microbial Landscapes and Dysregulated Microbiota–gu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiomes promote the polarization of M1/M2 macrophages, differentiation of Th1 lymphocytes, activation of cytotoxic T-cells, and upregulation of the expression of PD-L1 cointeractional molecule [6][7][8]. Intestinal microbiomes from the growth hormone-secreting pituitary adenoma (GHPA) patients promoted the mouse tumor growth, increased PD-L1 expression, and elevated the levels of PD-L1 in peripheral blood [9]. A great number of microbiotas including bacteria, fungi, and viruses colonize in the human stomach.…”
Section: Introductionmentioning
confidence: 99%
“…As a growth factor with potential capacity to promote tumor cell mitosis and growth, GH could regulate the tumor microenvironment (TME), epithelial–mesenchymal transition (EMT), DNA damage repair, tumor vascular distribution, and chemotherapy resistance, thereby initiating the occurrence and development of tumors ( 14 16 ). Recent studies also showed that GH could mediate the expression of PD-1/PD-L1 and regulate CD4 + and CD8 + T lymphocytes, which might modify the immunotherapy efficacy of tumors by mediating the PD-1/PD-L1 pathway and/or TME ( 17 19 ). In the present study, the predictive value of GH for ICI efficacy in AGC patients is innovatively evaluated.…”
Section: Introductionmentioning
confidence: 99%